Occurrence, Migration Behavior, and Environmental Burden of Phthalate Esters in Flooring Materials Used in Newly Renovated Chinese Homes - Ying Zhang; Li-Bo Chen; Hao-Yang Shen; Zi-Chao Wu; Ning-Zheng Zhu; Chong-Jing Gao; Ying Guo (Toxics, 2025)
Phthalic acid esters (PAEs), a class of synthetic semi-volatile organic compounds, are extensively incorporated into decorative materials. However, their specific occurrence, migration behaviors, and environmental impact on these materials—which comprise the largest surface areas in residential settings—remain insufficiently understood. This study investigated the distribution, emission dynamics, and environmental burdens of PAEs in flooring commonly used in Chinese households. The results showed that PAEs are widespread in flooring, with total concentrations ranging from 1220 to 166,000 ng/g (14,100 ng/g, median value). Solid wood flooring (55,900 ng/g) exhibited significantly higher PAE levels compared to engineered flooring (22,600 ng/g) and laminate flooring (4000 ng/g) (p < 0.05). Migration experiments revealed that solid wood flooring tended to continuously release PAEs, laminate flooring showed a pronounced capacity for PAE absorption, and engineered flooring exhibited both release and absorption behaviors. The initial PAE concentration is the dominant factor influencing migration rates, while the flooring type and substrate density also contribute to varying degrees. The estimated environmental burdens of PAEs resulting from flooring in newly renovated Chinese households ranged from 3.63 × 109 ng to 3.45 × 1011 ng, with a median value of 1.23 × 1010 ng. Households in the eastern and southwestern regions exhibited the highest PAE burdens, while the southern region showed the lowest. Socioeconomic factors such as residential floor area, number of rooms, household income, and renovation budget significantly influenced the environmental burden of PAEs derived from flooring.